1993
DOI: 10.1037/0022-006x.61.5.790
|View full text |Cite
|
Sign up to set email alerts
|

Self-help interventions for smoking cessation.

Abstract: Self-help interventions for smoking cessation are an important bridge between the clinical and public health approaches to smoking cessation. The current literature on self-help interventions is encouraging but incomplete. Although their quit rates are lower than those of more intensive programs, self-help interventions could have a large public health impact because of their potential for widespread distribution. Studies comparing self-help to more intensive treatment suggest that long-term cessation rates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 61 publications
4
53
0
3
Order By: Relevance
“…This is comparable with other studies of self-help interventions (Curry, 1993) as well as the results reported by Schneider and colleagues (1990). Additional progress toward the goal of cessation was suggested by a 75% increase over baseline in participants' reported intention to quit smoking, which is considered to be a primary goal of minimal contact=self-help interventions (Glynn, Boyd, & Gruman, 1990).…”
Section: Internet-enabled Help For Smoking Cessation 37supporting
confidence: 82%
“…This is comparable with other studies of self-help interventions (Curry, 1993) as well as the results reported by Schneider and colleagues (1990). Additional progress toward the goal of cessation was suggested by a 75% increase over baseline in participants' reported intention to quit smoking, which is considered to be a primary goal of minimal contact=self-help interventions (Glynn, Boyd, & Gruman, 1990).…”
Section: Internet-enabled Help For Smoking Cessation 37supporting
confidence: 82%
“…As reviewed in this article, the current evidence for the effectiveness of selfadministered treatment is mixed. With regard to self-administered behavioral programs, a review of studies conducted primarily in the 1980s reached the optimistic conclusion that wider dissemination of existing written self-help programs along with effective adjuncts such as personalization and outreach telephone counseling could have an significant public health impact (Curry, 1993). Rigorous meta-analyses of these studies along with more recently completed trials reached a similar conclusion.…”
Section: Conclusion/future Directionsmentioning
confidence: 88%
“…(e) What are the predictors of participation and success in self-help programs? Here, we briefly summarize the findings of that review (see Curry, 1993, for a detailed table summarizing 24 randomized evaluations of written self-help smoking cessation programs).…”
Section: Published Reviews Of the Self-help Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Efectuando uma revisão da maioria das investigações conduzidas sobre o comportamento de deixar de fumar, verifica-se que estas incluem seguimentos demasiado curtos, variando desde semanas até 6 meses (em média), estendendo-se alguns entre 12 meses e 18 meses, e muito raramente mais do que ano e meio (Curry, 1993). Stapleton (1998) refere também no seu estudo, que as recaídas surgiram até aos 3 anos e meio de seguimento, enfatizando a necessidade de mais estudos longitudinais, pois as recaídas continuam a verificar-se depois do final do seguimento da maioria dos estudos de cessação tabágica.…”
unclassified